2015
DOI: 10.3892/or.2015.4290
|View full text |Cite
|
Sign up to set email alerts
|

Trichosanthin suppresses the proliferation of glioma cells by inhibiting LGR5 expression and the Wnt/β-catenin signaling pathway

Abstract: Studies have indicated that trichosanthin (TCS), a bioactive protein extracted and purified from the tuberous root of Trichosanthes kirilowii (a well-known traditional Chinese medicinal plant), produces antitumor effects on various types of cancer cells. However, the effects of TCS on glioma cells are poorly understood. The objective of this study was to investigate the antitumor effects of TCS on the U87 and U251 cell lines. The in vitro effects of TCS on these two cell lines were determined using a Cell Coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…The garlic‐derived organosulfur compound diallyl trisulfide (DATS) blocks the activity of Wnt/β‐catenin pathway, consequently repressing proliferation, invasion, and angiogenesis of glioma cells (Q. Tao et al, ). Coincidently, trichosanthin (TCS) is extracted from traditional Chinese medicinal plant that contributes to glioma progression by reducing Wnt/β‐catenin signaling (Miao et al, ). As the normally consumed cruciferous vegetables, sulforaphane (SFN) effectively increases TMZ‐induced apoptosis because of downregulation of miR‐21 through Wnt/β‐catenin signaling in GBM (Lan, Pan, Yu, & Yue, ).…”
Section: Compounds Target the Wnt/β‐catenin Pathway In Glioma Developmentioning
confidence: 99%
“…The garlic‐derived organosulfur compound diallyl trisulfide (DATS) blocks the activity of Wnt/β‐catenin pathway, consequently repressing proliferation, invasion, and angiogenesis of glioma cells (Q. Tao et al, ). Coincidently, trichosanthin (TCS) is extracted from traditional Chinese medicinal plant that contributes to glioma progression by reducing Wnt/β‐catenin signaling (Miao et al, ). As the normally consumed cruciferous vegetables, sulforaphane (SFN) effectively increases TMZ‐induced apoptosis because of downregulation of miR‐21 through Wnt/β‐catenin signaling in GBM (Lan, Pan, Yu, & Yue, ).…”
Section: Compounds Target the Wnt/β‐catenin Pathway In Glioma Developmentioning
confidence: 99%
“…In the lineage tracing of mice, the LGR5 gene promoter was connected to the lacZ gene, which suggested that all the villous epithelial cells rooted from the LGR5-positive cells in the crypt, which lead to an affirmation that the intestinal stem cells are involved in the LGR5-positive cells [18,19]. In addition, in normal intestine, genetic transformation of LGR5-positive cells has revealed their potential to be tumor-initiating cells [20]. As is known to all, Wnt/β-catenin pathway, as a classic (Vector Laboratories, Burlingame, CA, USA).…”
Section: Introductionmentioning
confidence: 97%
“…Novelty, many biologically active ingredients of T. kirilowii were found to play important roles in lipid metabolism, anti‐inflammatory activity, and hypoglycemic activity (Iwabuchi, Kohno‐Murase, & Imamura, ; Shidoji & Ogawa, ). In addition, proteins extracted from T. kirilowii exert antitumor biological function (Li, Li, Zhang, Wang, & Zhang, ; Miao et al, ; Shaw, Lee, & Wong, ; Shi, Wong, & Shaw, ). TKP is a serine protease protein extracted from the fruit of T. kirilowii .…”
Section: Introductionmentioning
confidence: 99%